1999
DOI: 10.1103/physrevb.60.610
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of superconductivity inSr2RuO4caused by defects

Abstract: We have investigated depairing effects in Sr 2 RuO 4 , the unconventional superconductor in the layered perovskite structure. We prepared crystals of Sr 2 RuO 4 with very low levels of impurity elements, and systematically controled their superconducting transition temperature T c ranging from 1.5 to 0.6 K by adjustments of crystal growth conditions. The dependence of T c on the residual resistivity 0 in these crystals suggests that the defects are strong pair breakers, in addition to impurities. We further ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 12 publications
4
62
2
1
Order By: Relevance
“…While the slight deviation of the scattering phase shift from π/2 might be able to explain it [6], the calculated steep increase of κ 00 /T [3] is inappropriate for the description of Sr 2 RuO 4 . The critical resistivity, above which T c disappears, is about 1 µΩcm [18,19] and the corresponding critical κ/T is obtained by the Wiedemann-Franz law as 2.4 W/K 2 m, which is almost equal to our largest κ 00 /T . Since there is no clear reason for κ/T at T =0 K to become higher in the SC state than in the normal state, the increase of κ 00 /T with Γ expected in Ref.…”
Section: ∂∆(φ)mentioning
confidence: 80%
See 2 more Smart Citations
“…While the slight deviation of the scattering phase shift from π/2 might be able to explain it [6], the calculated steep increase of κ 00 /T [3] is inappropriate for the description of Sr 2 RuO 4 . The critical resistivity, above which T c disappears, is about 1 µΩcm [18,19] and the corresponding critical κ/T is obtained by the Wiedemann-Franz law as 2.4 W/K 2 m, which is almost equal to our largest κ 00 /T . Since there is no clear reason for κ/T at T =0 K to become higher in the SC state than in the normal state, the increase of κ 00 /T with Γ expected in Ref.…”
Section: ∂∆(φ)mentioning
confidence: 80%
“…The T c and the transition width δT c were defined at the peak temperature and the full width at half maximum of the imaginary part of the AC susceptibility, respectively (Table I). The difference in T c comes from the variation of the density of non-magnetic impurities, such as Al or Si [18], and/or crystalline defects [19]. The sys-tematic studies on the electrical resistivity ρ and resistive T c revealed that the suppression of T c is well described by the Abrikosov-Gorkov type equation [34],…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using known material parameters [4], and scattering time τ ∼ 10 −11 sec (mean free path ∼ 1 µm), extracted from the residual resistivity of similar samples [4,25], we obtain θ K ∼ 100 nanorad. This estimate is very close to the observed saturation signal of ∼ 65 nanorad.…”
mentioning
confidence: 99%
“…¿ÕÑÏÖ ÔÑÑÕÐÑÛÇÐËá ÖAEÑÄÎÇÕÄÑÓâáÕ ÍÂÍ AEÂÐÐÞÇ [51], ÕÂÍ Ë AEÂÐÐÞÇ ÒÓÇAEÞAEÖÜËØ ÓÂÃÑÕ [55,56]. ¥Îâ ÑÒÓÇAEÇÎÇÐËâ AEÎËÐÞ ÔÄÑÃÑAEÐÑÅÑ ÒÓÑÃÇÅ l РÑÔÐÑÄÇ ËÊÏÇÓÇÐËÌ ÑÔÕÂ-ÕÑÚÐÑÅÑ ÔÑÒÓÑÕËÄÎÇÐËâ r 0 ËÔÒÑÎßÊÑÄÂÎÂÔß ×ÑÓÏÖΠ[57].…”
Section: ¿××çíõþunclassified